Wind Phone, Operomanija: Notes on Vulnerability, Longing and Love (Sound Stage Screen, 2024)
Review of the phone booth opera Things I Didn’t Dare to Say, and It’s Too Late Now. World premiere: 1st December 2023, Lithuanian National Drama Theatre, Vilnius.